Subsurface life can modify volatile cycling on a planetary scale - Giovanelli, D. (2021)
The past decade of environmental microbiology has revealed that subsurface environments, both marine and continental, harbor one of the largest ecosystems of our planet, with diversity and biomass rivaling those of the surface. In addition, subsurface life has been recently shown to contribute significantly to the planet’s biogeochemistry, with microbial activity potentially playing an important role in controlling the flux and composition of volatiles recycled between the Earth’s surface and interior, which has broad implications for the search for life beyond our planet. Current efforts to discover extraterrestrial life are focused on planetary bodies with largely inhospitable surfaces, such as Mars, Venus, Europa, Titan, and Enceladus. In these locations, subsurface environments might provide niches of habitability, making the study of deep microbial life a priority for future astrobiological missions. Understanding how volatile elements are exchanged between planetary surfaces and interiors and the role of a subsurface biosphere in altering their composition and flux might provide a tractable target for defining planetary habitability and the detection of subsurface life forms.